Intraorbital neuromuscular choristoma adjacent to the optic nerve - Arie Perry, M.D; Jane W. Chan, M.D; Jennifer A. Cotter, M.D; Adam Bracha, M.D (Elsevier, 2017)
Neuromuscular choristoma is a rare tumor that incorporates mature skeletal muscle within fascicles of peripheral nerve. The etiology is poorly understood, yet most present in large nerves of children, with a tight link to post-operative fibromatosis recently appreciated. Herein, we report an exceptional intra-orbital example in a 53-year-old man with optic nerve compression.